Aeromonas spp. Em água de pisciculturas da região da baixada ocidental Maranhense - Lima Silva, Rejeana Marcia [UNESP]; Rossi Junior, Oswaldo Durival [UNESP]; Costa, Francisca Neide; Chaves, Nancylene Pinto; do Nascimento, Danielle Lopes; Kamimura, Bruna Akie [UNESP] (Inst Pesca, 2010)
Among the widely distributed bacterial agents in the aquatic ecosystem, can be outstanding the family Aeromonadaceae detected such in fish as in the water of this system. This study intended to verify the occurrence of Aeromonas spp. in pond water of fishfarms located in Occidental Lowland Region of Maranhao. Twelve properties located in Pinheiro, Palmeirandia and Perimirim cities had been selected. The harvest of the samples occurred in the period from October, 2008 to March, 2009. A total of 48 pond water samples were harvested. Four water samples of each fishfarm. Aeromonas were confirmed in 100% of the samples. The 89 isolate identified had been classified in three species, A. hydrophila (88%), A. caviae (9%), A. veronii sobria (3%). The pond waters of the fishfarms analyzed presented contamination with potentially pathogenic species of aeromonas which represents risk for people's health, especially for the organisms cultivated in these properties.
Aeromonas spp. in water of fishfarms in occidental lowland region of Maranhão
Keywords: Bacteria; Public health; Aquaculture